ASPEK PAJAK DAN DAMPAK KETERLAMBATAN KEPEMILIKAN NPWP PRIBADI DENGAN DIBERLAKUKANNYA UNDANG-UNDANG NO. 28 TAHUN 2007 DAN UNDANG-UNDANG NO. 36 TAHUN 2008 - Susyanti, Jeni (Fakultas Ekonomi, UIN Maliki Malang, 2009)
The society’s obligation to support the government continuity is through the tax. Having NPWP is everyone’s obligation, whether he is individual who conducts business activities, does free work, or works as employee. By the implementation of Undang Undang No. 28 tahun 2007 regarding the General Rules and Tax Explanation and Undang-undang No.36 tahun 2008 regarding the Income Tax, there is a discrimination of tax applied to an individual who has NPWP against those who doesn’t.